Transitivity Process in Joko Widodo™s Inauguration Speech - Siringo-ringo, Alfrin Juniarto; Meisuri, Meisuri (Universitas Negeri Medan, 2021)
The thesis deals with Transitivity Process in Joko Widodo™s Inauguration Speech. The objectives of this study were to find out the types of transitivity process used, and to describe transitivity revealed in Joko Widodo™s Inauguration Speech. This study was conducted by using the descriptive qualitative method. The data of the study were the clauses that spoken by Joko Widodo™s in the Inauguration Speech. The data analyzed were taken by listing and tabulating the data. The data were analyzed based on the theory proposed by Halliday™s. The findings indicated that there are transitivity process which consists of six significant types, those are: material, mental, relational, behavioral, verbal, and existential. There are material process is (49,46%), relational process (32,25%), verbal process (6,45%), mental process (5,37%), existential (4,30%), and behavioral (2,15%). The transitivity process reveals that Joko Widodo™s attempts to construct the ideology of democracy during his speech.